2002
DOI: 10.1034/j.1399-3054.2002.1140206.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for far‐red light to maintain secondary needle extension growth in northern but not southern populations of Pinus sylvestris (Scots pine)

Abstract: Extension growth of secondary needles is under photoperiodic control in Pinus sylvestris. To test for the effects of far-red light on maintaining this extension growth, seedlings of six populations originating from latitudes between 57 degrees and 67 degrees N were raised for 11 weeks in continuous incandescent (metal halogen) light at 300 &mgr;mol m-2 s-1 and 20 degrees C and then transferred at the same temperature to a daily regime of 8 h incandescent light (230 &mgr;mol m-2 s-1) followed by a 16 h day exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
6
35
0
2
Order By: Relevance
“…However, in countries at mid-range latitudes like Spain natural reproduction requires that older trees protect young trees against heat and water stress in the summer (personal communication by C. Gracia, University of Barcelona, Department of Ecology and CREAF, the Centre for Ecological Research and Forestry Applications). This finding is supported by field experiments reported by Clapham et al (2002) and Sanchez-Gomez et al (2006).…”
supporting
confidence: 80%
“…However, in countries at mid-range latitudes like Spain natural reproduction requires that older trees protect young trees against heat and water stress in the summer (personal communication by C. Gracia, University of Barcelona, Department of Ecology and CREAF, the Centre for Ecological Research and Forestry Applications). This finding is supported by field experiments reported by Clapham et al (2002) and Sanchez-Gomez et al (2006).…”
supporting
confidence: 80%
“…Differences in FR light requirement for growth extension were shown by latitudinal ecotypes of Salix pentandra (Junttila and Kaurin, 1985), Picea abies (Clapham et al 1998) and Pinus sylvestris (Clapham et al 2002). When the day-length was extended with FR-poor lamps, the southern ecotypes (south of 61 -64ºN) continued to grow while the northern ones ceased growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using light sources enriched in red (R) or far-red (FR) light demonstrated a demand for FR light to sustain growth in angiosperms as well as gymnosperms (Håbjørg 1972;Junttila and Kaurin 1985;Clapham et al 1998aClapham et al , 2002. This trait also shows a clinal variation.…”
Section: Relative Importance Of Photoperiod and Light Quality Differsmentioning
confidence: 95%
“…Accordingly, similar to photoperiodic control of flowering, both phyA and phyB probably act in photoperiodic control of shoot elongation. Like SD plants, southern ecotypes of woody species respond to night breaks in a R-FR reversible manner (Clapham et al 1998a(Clapham et al , 2002. Thus, since low fluence R/FR reversibility is a characteristic for light stable phytochromes, such as phyB, a domination of a phyBlike-based system in southern ecotypes can be hypothesized.…”
Section: Relative Importance Of Photoperiod and Light Quality Differsmentioning
confidence: 98%